Transgenerational maintenance of transgene body CG but not CHG and CHH methylation - Dalakouras, Athanasios; Wassenegger, Michael (Epigenetics, 2012)
In plants, RNA-directed DNA methylation (RdDM) can target both transgene promoters and coding regions/gene bodies. RdDM leads to methylation of cytosines in all sequence contexts: CG, CHG and CHH. Upon segregation of the RdDM trigger, at least CG methylation can be maintained at promoter regions in the progeny. So far, it is not clear whether coding region methylation can be also maintained. We showed that the body of Potato spindle tuber viroid (PSTVd) transgene constructs became densely de novo methylated at CG, CHG and CHH sites upon PSTVd infection. In this study, we demonstrate that in viroid-free progeny plants, asymmetric CHH and CHG methylation was completely lost. However, symmetric CG methylation was stably maintained for at least two generations. Importantly, the presence of transgene body methylation did not lead to an increase of dimethylation of histone H3 lysine 9 or a decrease of acetylation of H3. Our data supports the view that CG methylation can be maintained not only in promoters but also in the body of transgenes. They further suggest that maintenance of methylation may occur independently of tested chromatin modifications.